Pembuatan Kursi Antropomteri Berbasis Sensor Hc-Sr 04 - Hapyansyah, Dio; Sari, Resy Kumala; Musridho, Raja Joko (Journal on Pustaka Cendekia Informatika, 2023)
The industrial revolution is currently entering the industrial 4.0 stage where it is experiencing its peak, with the birth of digital technology which is very useful for human life throughout the world. The Industrial Revolution 4.0 is colored by artificial intelligence, super computers, genetic engineering, nanotechnology, automatic cars and innovation. the data used in making anthropometric chairs is secondary data. This data is obtained from research that has been carried out by previous studies using the House of Quality (HOQ) method. The data taken is in the form of sketches and product designs for anthropometric chairs based on the HC-SR04 sensor. Making anthropometric chairs using the Operation Process Chart (OPC) Diagram Using the HC-SR04 sensor-based anthropometric chair is faster and more accurate when taking measurements of the human body compared to using a meter or manually